The genus Syllis (Polychaeta: Syllidae: Syllinae) in the southern Mexican Pacific, with the description of two new species and three new records - Oropeza, Diana L. Salcedo; San Martín, Guillermo; Solís-Weiss, Vivianne (Zootaxa, 2012)
As part of a study dealing with polychaetes (Annelida: Polychaeta) from soft bottoms of the western coasts of AcapulcoBay, southern Mexican Pacific, 574 specimens of the genus Syllis Lamarck, 1818 were analyzed. Nine species are report-ed, of which Syllis garciai (Campoy, 1982) and Syllis glarearia (Westheide, 1974) are new records for the Mexican Pa-cific. Syllis magnipectinis (Storch, 1967), described from the Red Sea, is newly reported in the eastern Pacific; notes onits morphological variations and its distribution range are herein included. Additionally, two new species of Syllis are de-scribed: S. antoniae n. sp., is closely related to S. vivipara Krohn, 1869, but it has bidentate falcigers with a smaller sub-distal tooth and some falcigers with coarse spines on the edge. S. deleoni n. sp., is characterized by having bidentate falcigers with broad teeth and coarse spines and the body densely covered with papillae.